2015
DOI: 10.1093/aje/kwv016
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Epidemiology of Intimate Partner Violence: Do Neighborhoods Matter?

Abstract: We examined whether neighborhood-level characteristics influence spatial variations in the risk of intimate partner violence (IPV). Geocoded data on IPV cases with associated protection orders (n = 1,623) in the city of Valencia, Spain (2011-2013), were used for the analyses. Neighborhood units were 552 census block groups. Drawing from social disorganization theory, we explored 3 types of contextual influences: concentrated disadvantage, concentration of immigrants, and residential instability. A Bayesian spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
106
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(120 citation statements)
references
References 61 publications
7
106
0
7
Order By: Relevance
“…The risk of violence can increase among immigrant women due to their legal and economic situation and to different barriers to accessing information and support services (Martinez-Roman, Vives-Cases and Pérez-Belda, 2017). Intimate partner violence was found to be higher in physically disordered and decaying neighborhoods and in neighborhoods with low educational and economic status levels, high levels of public disorder and crime, and high concentrations of immigrants (Gracia et al, 2015).…”
Section: Prevalence Of Violence Against Migrant Womenmentioning
confidence: 94%
“…The risk of violence can increase among immigrant women due to their legal and economic situation and to different barriers to accessing information and support services (Martinez-Roman, Vives-Cases and Pérez-Belda, 2017). Intimate partner violence was found to be higher in physically disordered and decaying neighborhoods and in neighborhoods with low educational and economic status levels, high levels of public disorder and crime, and high concentrations of immigrants (Gracia et al, 2015).…”
Section: Prevalence Of Violence Against Migrant Womenmentioning
confidence: 94%
“…Research has found that concentrated disadvantage is the factor most strongly associated with crime, even after controlling for individual characteristics [1,8]. Immigration has also been related to crime rates, and previous research has shown that higher levels of ethnic heterogeneity are related to higher levels of crime [1,9,10]. Residential instability is also a relevant factor in social disorganization theory.…”
Section: Introductionmentioning
confidence: 99%
“…Most research has focused on residential burglary [13][14][15], juvenile delinquency [16,17], homicides [1,18,19], and robbery and assaults [18,19]. Interest is also growing in studying this relationship in other crimes that tends to occur 'behind closed doors' [20] such as intimate partner violence [9,10] or child maltreatment [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small but growing body of research has adopted Bayesian spatial modeling approaches in crime analysis [10][11][12][13][14][15][16][17]. For example, researchers using Bayesian spatial models have investigated contextual influences on domestic violence [12,15,18], juvenile offenders [14] and property crime [13].…”
Section: Introductionmentioning
confidence: 99%